2021
DOI: 10.3390/socsci10080280
|View full text |Cite
|
Sign up to set email alerts
|

“Divide, Divert, & Conquer” Deconstructing the Presidential Framing of White Supremacy in the COVID-19 Era

Abstract: Based on the analysis of President Donald J. Trump’s social media, along with excerpts from his speeches and press releases, this study sheds light on the framing of white supremacy during the first months of the COVID-19 pandemic in the United States. Our findings reveal that the triad of divide, divert, and conquer was crucial to Trump’s communications strategy. We argue that racist nativism—or racialized national threats to American security—is key to comprehending the external divisiveness in this strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…During the last year of his presidency, Trump's xenophobic narrative was clearly seen in his vilification of Asian communities, especially in his framing of COVID-19 as the "Chinese virus" and the "Kung fu virus." Research has shown how such xenophobic rhetoric led to racial and ethnic hate as well as verbal and physical violence against Asian populations in the United States and overseas (Gover, Harper, and Langton 2020;Louie and Viladrich 2021;Viladrich 2021).…”
Section: Conceptual Framework: Deconstructing Xenophobia During Trump...mentioning
confidence: 99%
“…During the last year of his presidency, Trump's xenophobic narrative was clearly seen in his vilification of Asian communities, especially in his framing of COVID-19 as the "Chinese virus" and the "Kung fu virus." Research has shown how such xenophobic rhetoric led to racial and ethnic hate as well as verbal and physical violence against Asian populations in the United States and overseas (Gover, Harper, and Langton 2020;Louie and Viladrich 2021;Viladrich 2021).…”
Section: Conceptual Framework: Deconstructing Xenophobia During Trump...mentioning
confidence: 99%
“…Despite elevated risk for experiencing pandemic stressors and constrained resources, prior research suggests that undocumented students and US citizens with undocumented parents are not faring particularly worse in COVID-related physical and mental health outcomes than their US-born counterparts with lawfully present parents [ 28 ]. Building on this research, we focus on Latinas/os/xs because this group may experience a unique relationship between self/parental immigration status and COVID-related mental health outcomes due to racist-nativist discourse that casts Latinas/os/xs as undocumented immigrants who are COVID-19 carriers and undeserving of aid [ 29 , 30 ]. Latinas/os/xs also have higher age-specific death rates for COVID-19 compared to Whites and, in California, are 8.1 times more likely to live in households at high risk of exposure (23.6% versus 2.9%) and are overrepresented in caseloads (3,784 per 100,000 people versus 1,112) [ 15 , 31 ]; this suggests that Latinas/os/xs may experience unique pandemic-related stressors that may strain their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also begun exploring the beliefs, perceptions, and experiences of marginalized, underserved, rural communities across cultures (Alonzo & Popescu, 2021; Bloom et al, 2021; De Fuentes-Vicente et al, 2021). Recent scholarship examines COVID information access and navigation for Black women, Korean immigrant women, d/Deaf ASL-users, and other groups, investigates Black and Latinx interpretations of community-targeted COVID health messaging, and assesses pandemic discourse for various western and non-western populations (Ahinkorah et al, 2020; Alsan et al, 2021; Chandler et al, 2021; Jang & Jung, 2021; Khan et al, 2020; Rai et al, 2021; Panko et al, 2021). Still, more research is needed to capture and delve into the impact and experiences of marginalized individuals and communities.…”
Section: Introductionmentioning
confidence: 99%
“…Propagated through news and social media, such accusations fueled discrimination and hate toward Asian Americans (Tessler et al, 2020). On a related note, wrongful accusations that immigrants imported COVID similarly underscored existing racist attitudes, contributing to the marginalization (Louie & Viladrich, 2021). And, of course, one can't ignore the link between pandemic discrimination and the protests for justice against police brutality.…”
mentioning
confidence: 99%